(untitled) (Indian Journal of Animal Production and Management, 2024)
A field study was conducted in Junagadh district of Gujarat to ascertain the health care practices followed by Jaffarabadi buffalo owners and data were collected from randomly selected 320 respondents through personal interview with the help of structured interview schedule. The present study revealed that about 63.12 and 17.50 percent of the respondents regularly vaccinated their buffaloes against Foot and Mouth Disease and Haemorrhagic Septicaemia disease, respectively. None of the respondents vaccinated and tested their buffaloes against brucellosis. Only 18.13 percent of the respondents practiced deworming to their buffaloes at regular interval and followed various practices (spraying, dusting and injectable drugs) for control of ecto–parasites (81.56%) and cleaned animal sheds (76.57%). Only 22.82 percent of the respondents informed that they treated their sick buffaloes by veterinarian. All the respondents washed hind quarters of buffalo after drop of placenta. Most (83.75%) of the respondents kept diseased animals together with healthy ones and majority (70.94%) of the respondents removed the dung twice in a day from animal sheds.